Laser welding process in PP molding parts: evaluation of seam performance - Oliveira, N. (2016)
New welding technologies have been implemented in the polymer processing industry in the past few years. Additionally, the most used polymer in complex products is polypropylene. This material can also be mixed with several additives, namely glass fiber, carbon nanotubes, etc. This compatibility with different additives allows products with characteristics that range from impact absorption to electrical conductivity. When it is necessary to join components in PP, they can be welded by hot plate, ultrasonic or laser welding. The present research aims at studying the influence of variables capable of influencing the final quality of the seam, namely those related to injection molding, such as mold temperature and cooling time, laser welding variables and materials, and how laser welding interacts with PP. The results showed that the most influential variables were mold temperature, laser velocity and laser diameter. The seams were analyzed using optical microscopy. They showed perfect contact between the components, despite the high standard variation present in the mechanical tests.